Militarism or peace and justice: Psychology at the crossroads of climate change - Değirmencioğlu, Serdar M. (PINS-Psychology in Society, 2022)
Psychological research on climate change has shifted its focus toward the way climate change influences psychological well-being. An exclusive focus on the consequences of climate change is misleading because there is an urgent need to address causes of climate change. The leading institutional user of fossil fuel and the single largest producer of greenhouse gases is a military force. The common argument that individuals must think differently about climate change also applies to psychologists: Psychologists must start considering the impact of militarism on climate change and abandon their reluctance to address military pollution, environmental destruction, and the environmental impact of nuclear weapons. This reluctance is linked with the long-standing militarism within mainstream psychology. Psychologists cannot continue ignore or ally with militarism while militarism produces two global threats: A total nuclear war and climate change. Psychologists can find a more meaningful role in any society focusing on peace, justice and human rights, rather than militarism and national security. In the context of the environment, psychologists must choose to defend the planet, which is home to all. In the context of climate change, psychologists can chart a meaningful course of action only if they focus on environmental justice.